Spiral of Decline or "Beacon of Hope:" Stories of School Choice in a Dual Language School. - Timothy Marc Pearson; Jennifer R. Wolgemuth; Soria E. Colomer (Arizona State University, 2015)
Public schools in some areas of the U.S. are as segregated as they were prior to court-ordered busing, in part due to school choice policies that appear to exacerbate extant segregation. In particular, Latina/o students are increasingly isolated in schools characterized as being in cycles of decline. Our case study of one such school is based on a reanalysis of interview, focus group, and survey data from three research and evaluation projects. We constructed accounts of parents' decisions to leave and remain at Martinez Elementary, a segregated dual language school experiencing increases in Latina/o and low socio-economic student enrollment and decreasing statewide standardized test scores. Interpreting Latina/o and White parents' accounts through LatCrit theory, we sought to understand their choices to attend this school as counterstories that illustrate conflicting forces influencing Martinez, including high parent satisfaction and interest convergence between White and Latina/o parents. These stories depict a more hopeful account of a school resisting decline, yet only the adoption of managed school choice policies may be powerful enough to counter the school's segregation.